LATAR BELAKANG SOSIAL EKONOMI MASYARAKAT ISLAM ( Studi Kasus Tukang Perahu di Desa Brodot Kecamatan Bandarkedungmulyo Kabupaten Jombang Propinsi Jawa Timur ) - Syamsul Huda (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) UIN Datokarama Palu, 2014)
This study discusses the socio-economic background of the Islamic community who work as boatmen and farmers in the Brodot Village Bandarkedungmulyo District Jombang of East Java Province. This study is a qualitative study, which seeks to explore aspects of the economic and social aspects Brodot villagers who worked as a boatman and farmers. Data collection in this study was done in two ways: observation and interviews. The results of this study indicate that the profession as a farmer who cultivated by villagers Brodot Bandarkedungmulyo Jombang District of East Java Province, with an income about 300,000 rupiah per month is not sufficient for their daily needs. Therefore, to anticipate the needs of everyday life, they look for other income that is as boatman with an average income of 250,000 rupiah per month. With the extra they can cover their daily life with family even lived a simple life and mediocre